Comparative Analysis of EOQ Method, POQ Method, and Min-Max Method in Controlling Inventory of Subsidized NPK Phonska Fertilizer Raw Materials at PT Petrokimia Gresik - Khofidatul Sesilia; Moh. Jufriyanto; Akhmad Wasiur Rizqi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
PT Petrokimia Gresik is the most comprehensive fertilizer manufacturer in Indonesia, and it produces a wide range of fertilizers and chemicals for agro-industry solutions. One of its products, NPK Phonska fertilizer, is always the product with the highest demand every year. In 2023, the demand for this fertilizer reached 1,972,380.55 tons. The main problem that often occurs is the overstocking and stocking out of raw materials. This condition not only results in increased storage costs but also threatens production continuity. Therefore, optimal inventory control is the company's main goal, which is to ensure the availability of raw materials in a timely manner and minimize costs. This study aims to find the most effective inventory control method in overcoming these problems. The EOQ (Economic Order Quantity) and POQ (Periodic Order Quantity) methods were chosen as alternative solutions. This research uses quantitative methods with data collection through field observations. The results showed that the most right inventory control method to reduce total inventory costs is the EOQ method, with a total cost of Rp7,043,999,215. This figure is lower than the POQ method of Rp11,071,943,308 and the Min-Max method used by the company of Rp23,217,085,977. The EOQ method is proven to be more efficient in managing inventory, resulting in cost savings of up to 69.7% or Rp16,173,086,762. Therefore, the application of the EOQ method is a good choice to be implemented in the company. Keywords: Raw Material Inventory, Inventory Control Methods, Economic Order Quantity (EOQ), Periodic Order Quantity (POQ), Minimum-Maximum (Min-Max)